Loyalty, royalty and obligation: 'Good shepherds under law' - Hordern, J (Wiley, 2016)
This article explores how conversation between the thought of certain Islamic and Christian thinkers, such as Agapetos, Gregory the Great and Sa`di, sheds light on how loyalty and obligation function within institutions of kingship and in political experience more generally. The argument shows how a focus on Late Antique notions of kingship is a particularly fruitful focus for conversation between Islamic and Christian political thought. The exposition of texts pays particular attention to political concepts’ dependence on salvation historical understanding in order to examine ways of conceptualising and generating the interrelation of obligation and criticism that commonly constitutes the interrelation of peoples with rulers. With Hellenism as the bridging tradition through which diverse forms of Islamic and Christian political thought pass, the argument explores the moral psychology of institutions of kingship, especially affections such as fear and love by which political loyalty and obligation are said to operate. The conversation concludes by developing a notion of ‘good shepherds under law’, evoked both by Christian interpretations of the Davidic tradition and Islamic interpretations of the relation of ruler to ruled, summarised as a ‘pastoral contract’. These political interpretations, while not reducible to each other, together build a bridge to support that tense communion through which better understanding of political life may be gained. In exploring the psychology of leadership as an elemental phenomenon of political life, the argument signals beyond the premodern contexts from which the authors discussed are principally drawn towards interpretation of present-day political experience.